2017
DOI: 10.4018/ijaeis.2017100103
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning Methods for Classification and Prediction of Groundwater Quality Using a Small Data Record

Abstract: The objective of this study was to consider the efficiency of support vector machine (SVM) and artificial neural network (ANN) for the classification and prediction of groundwater quality using a small data record in Malayer, Iran. For this purpose, 14 groundwater quality variables that had been collected from 27 groundwater sampling wells were used. Cluster analysis discriminated the total sampling stations into two groups. The classification was implemented by SVM using polynomial and RBF kernel methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The study also showed that the SVM model is a fast, reliable, and cost-effective AI technique. The feasibility of AI techniques in groundwater quality simulation has been evaluated by numerous scholars and such studies have produced efficient performances [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that the SVM model is a fast, reliable, and cost-effective AI technique. The feasibility of AI techniques in groundwater quality simulation has been evaluated by numerous scholars and such studies have produced efficient performances [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [10] showed that an appropriate choice of regression algorithm and input parameters allows us to build accurate surrogates for simulations in additive manufacturing. The authors of [11] used a cluster analysis approach to generate surrogate data in the medical domain. In [12], the authors applied a deep neural network (DNN) to integrate similarity features and perform learning to predict software defects.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, different approaches to predicting, detecting, and assessing oil spills have been proposed to reduce their consequences [28][29][30]. Depending on the types of prediction, detection, and assessment problems being solved and the answers required, particular classification [11] or regression [31] algorithms are used. Both classes of algorithms (classification and regression) are used to predict outcomes in Supervised ML (SML), and both use labelled datasets to train algorithms [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations